Inside Front Cover: Anisotropic transition metal–based nanomaterials for biomedical applications (View 4/2021). Issue 4 (29th August 2021) - Xu, Min; Song, Yiling; Wang, Jinping; Li, Nan
Abstract : Transition metal‐based nanoparticles have attracted more and more attention in biomedicine, owing to their special characteristics that arise from finite‐size and surface effects, like intense and broad light absorption, strong oxidation ability, catalytic activity, and robust mechanical properties. In article number 20200154, Nan Li, Jinping Wang and their co‐workers summarize in detail the mechanism and advantages of three main shape categories of anisotropic transition metal‐based nanomaterials in biomedical applications, including one‐dimension (1D, e.g., nanowire), two‐dimension (2D, e.g., nanosheet), and three‐dimension (3D, e.g., nanorod, nanocube, and nanoflower) anisotropic shape. In addition, the critical challenges and prospects of this field will be also proposed and discussed.